2020
DOI: 10.12669/pjms.37.1.2956
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of Chest CT and Initial Real-Time RT-PCR in COVID-19 Infection

Abstract: Objectives: To evaluate the diagnostic value of the rtRT-PCR test and CT in patients presenting with typical clinical symptoms of COVID-19. Methods: The study with the participation of four center in Turkey was performed retrospectively from 20 March-15 April 2020 in 203 patients confirmed for COVID-19. The initial rtRT-PCR test was positive in 142 (70.0%) of the patients (Group-I) and negative in 61 patients (Group-II). Results: The mean age of the patients in Group-I was 49.7±18.0 years and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…It has been reported that the missed diagnosis of COVID-19 by CT is low (3.9%) (13). CT positivity was reported as 64% in the study of Kostaoğlu et al (12). In our study, on thoracic CT, typical appearance compatible with COVID-19 was present in 189 (11.9%) cases.…”
Section: Betweensupporting
confidence: 53%
See 2 more Smart Citations
“…It has been reported that the missed diagnosis of COVID-19 by CT is low (3.9%) (13). CT positivity was reported as 64% in the study of Kostaoğlu et al (12). In our study, on thoracic CT, typical appearance compatible with COVID-19 was present in 189 (11.9%) cases.…”
Section: Betweensupporting
confidence: 53%
“…In the study of Jin et al, 37% were reported to have at least one comorbidity (18). In the study of Kostaoğlu colleagues, the most common comorbidity was hypertension (12). In a study conducted in Iran, diabetes, chronic respiratory disease, and hypertension were the most common comorbidities (20).…”
Section: Betweenmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, a retrospective cohort analysis in New York by Zacharioudakis et al (n = 42) showed that a three-fold increase in Ct value denoted a correlation with a 0.15 improvement in terms of genomic load on Sequential Organ Failure Assessment (SOFA) score [100][101][102][103][104][105][106]. Another larger study with 192 patients revealed that patients who died in hospital had significantly lower Ct values than those who were discharged alive [100].…”
Section: Disease Severitymentioning
confidence: 99%
“…Poor prognosis of COVID-19 case management is reported due to various co-morbidities. Prolonged viral shedding is seen in mild COVID-19 patients with older age, hypertension, and diabetes mellitus [13,101].…”
Section: Co-morbiditiesmentioning
confidence: 99%